Continental Survey of Access to Diagnostic Tools and Endovascular Management of Aneurysmal Subarachnoid Hemorrhage in Africa - Dokponou, Yao Christian Hugues; Kotecha, Jay; Bandyopadhyay, Soham; Erhabor, Joshua; Ooi, Setthasorn Zhi Yang; Egiz, Abdullah; Boutarbouch, Mahjouba; Dalle, David Ulrich; Higginbotham, George; Thioub, Mbaye; Sichimba, Dawin; Bankole, Nourou Dine Adeniran; et al. (Frontiers in Surgery, 2021)
Rationale: Interventional neurovascular procedures are effective in lowering the burden of mortality and complications resulting from aneurysmal subarachnoid hemorrhage (aSAH). Despite the wide uptake of interventional neurovascular procedures in high-income countries, access to care in low- and middle-income countries remains limited, and little is known about accessibility in Africa. In this survey, we decided to assess access to diagnostic tools and treatment of aSAH in Africa. Methodology: A Google form e-survey was distributed to African neurosurgery centers accepting responses from January 4th to March 21st 2021. Data on accessibility to diagnostic tools, treatment methodologies, and interventional neuroradiology personnel in African centers were collected. Ninety five percent confidence intervals were computed for each variable. Results: Data was received from 36 neurosurgical centers in 16 African countries (16/54, 30%). Most centers were public institutions. Ninety four percent of the centers had the necessary resources for a lumbar puncture (LP) and a laboratory for the diagnosis of aSAH. Most centers had at least one computed tomography (CT) scanner, 81% of the centers had access to CT angiography and some had access to conventional angiography. Forty seven percent of the centers could obtain a head CT within 2 h of presentation in an emergency. Sixty one percent of centers provided clipping of intracranial aneurysms whilst only 22% of centers could perform the endovascular treatment. Sixty four percent of centers did not have an endovascular specialist. Conclusion: This survey highlights health inequity in access to endovascular treatment for aSAH. Lack of diagnostic tools to identify an aneurysm and a shortfall of qualified endovascular specialists are prime reasons for this. Our findings can inform health system strengthening policies including the acquisition of equipment and capacity building in Africa.